Theoretical Interpretations Of Views On Freedom Of Speech And Information. - Usmonov Farkhod Lapasovich (Periodica Journal, 2025)
This article provides a detailed overview of existing approaches to understanding, describing, and linking this phenomenon with contemporary social phenomena, taking into account the lack of a single concept that expresses the categorical and methodological meaning of the concept of freedom of speech and information and related concepts. Approaching the issue from the perspective of historicity and modernity, tradition and renewal allows us to correctly understand the problems in this area and find effective ways to solve them
Keywords: speech; information; politics; economy